Finkenwalde and Harnack’s influence in Bonhoeffer’s call for a “New Monasticism” - Pavlík, Martin (Stellenbosch Theological Journal, 2023)
The objective of the article is to briefly look into the thoughts stemming from the period in which Dietrich Bonhoeffer stood at the forefront of the illegal seminary run by the Confessing Church at Finkenwalde (from 1935 to 1937) and also to verify the hypothesis that his call for “new monasticism” was influenced by the ideas of Adolf von Harnack (1851–1930) on Christian asceticism and monasticism. Bonhoeffer made this call in one of his letters shortly before he became the head of the Finkenwalde seminary where he emphasized life in community and deep spiritual formation in addition to consistent theological education. Harnack considered the absence of monasticism “in the evangelical sense of the word” a fundamental deficiency in Protestantism. The article validates that the examination of the common themes of these two authors about monasticism contributes to a deeper understanding of Bonhoeffer’s Finkenwalde theology.